Wahrnehmungsvignetten. Phänomenologisch-reflexives Denken und professionelle Haltung Studien- und Arbeitsbuch - Barth, Ulrike (Verlag Julius Klinkhardt, 2023)
Perceptual vignettes originate from a phenomenological method of pedagogical practice and research. It includes perceptions, descriptions and reflection phases for professional inclusive attitude development and diagnostics. The processual work with perceptual vignettes challenges us to put aside ideal-typical patterns, categorisations of all kinds, judgements about prognoses and to look more closely at the individual and special situation of a person. The volume is designed as a study and workbook and includes theoretical basics, practical applications of the method and topic-specific exercises for perceiving, writing and reflecting.